Effect of Blanching on Sorption Isotherms of Spinach - Zambare, A V; Foke, V N; Kakade, S N; Mulani, S L (Journal of Agricultural Engineering, 2010)
A study was conducted to determine the effect of blanching on moisture adsorption and desorption characteristics of spinach. Moisture sorption was determined by gravimetric method. Different saturated salt solutions were prepared to provide constant relative humidity environments. Four spinach samples (unblanched, unblanched dried, blanched and blanched dried) were kept at 3 temperatures (30 degree C, 40 degree C and 60 degree C) with corresponding 5 relative humidity levels (10.95 to 92.31%). It was observed that for all samples, equilibrium moisture content (EMC) of spinach increased with increase in relative humidity at constant temperature. At constant relative humidity levels, EMC decreased with increase in temperature. The adsorption EMC of the spinach was lower than the desorption EMC for blanched as well as unblanched spinach for all temperature and relative humidity ranges. The blanched dried spinach exhibited lowest EMC at all temperature and relative humidity ranges.